2007
DOI: 10.2460/javma.231.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury in horses: 34 cases (1994–2004)

Abstract: Results suggest that prognosis for survival in horses with acute TBI may be more favorable than previously reported. Among horses with TBI, persistent recumbency and fractures involving the basilar bones were associated with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…This is in agreement with other reports where radiographs were a less suitable method for reaching a diagnosis of skull fractures (Feary et al . ). Advanced imaging techniques have proven to be useful in providing information about extension of damage and brain involvement (Feige et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is in agreement with other reports where radiographs were a less suitable method for reaching a diagnosis of skull fractures (Feary et al . ). Advanced imaging techniques have proven to be useful in providing information about extension of damage and brain involvement (Feige et al .…”
Section: Discussionmentioning
confidence: 97%
“…Primary lesions have an impact on clinical course and prognosis because of their often nonreversible nature leading to permanent neurological deficits, whilst therapeutic interventions are aimed at reducing the inflammatory response and secondary injury (Feary et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Some authors (MacKay ; Feary et al . ) affirm that brain contusion, laceration and bleeding are most likely when there is a fracture of overlaying bone. Magnetic resonance imaging revealed findings compatible with the presence of a ‘ping‐pong fracture’ of the right parietal bone, due to direct impact to the bone.…”
Section: Discussionmentioning
confidence: 92%
“…An impact to the head can cause transient bony deformation or fracture of the bone as previously reported (MacKay ; Feary et al . ). Mackay () reported that the effects of trauma were localised to the area of the brain adjacent to and opposite the site of impact causing coup and contrecoup lesions, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation